2014
DOI: 10.1039/c3pp50437a
|View full text |Cite
|
Sign up to set email alerts
|

Photochemical ligand ejection from non-sterically promoted Ru(ii)bis(diimine) 4,4′-bi-1,2,3-triazolyl complexes

Abstract: Complexes of the form [Ru(diimine)2(btz)](2+) (btz = 1,1'-dibenzyl-4,4'-bi-1,2,3-triazolyl) are observed to undergo photochemical ejection of the btz ligand in the absence of any promotion through steric congestion to generate cis-bis(solvent) complexes [Ru(diimine)2(solvent)2](2+).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
36
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 30 publications
(41 citation statements)
references
References 22 publications
4
36
0
1
Order By: Relevance
“…These energies can be determined or inferred spectroscopically, electrochemically and computationally and as [Ru(N^N) 3 ] 2+ complexes invariably have a highest occupied molecular orbital of predominantly metallic 4d character, and hence effectively the same ground state, these excited state energies can be readily compared). Work in our laboratory, [26][27][28] and those of others, [29][30][31][32] has shown that complexes containing 1,2,3-triazole rings that lack such steric promotion can also lead to photochemical reactivity, possibly through destabilisation of the 3 MLCT state with respect to the 3 MC state when compared to those states of the archetypal complex [Ru(bpy) 3 ] 2+ . We recently reported the series of complexes [Ru(bpy) 3-n (btz) n ] 2+ (btz = 1,1'-dibenzyl-4,4'-bi-1,2,3-triazolyl, n = 1 to 3) 33 in which an increasing number of btz ligands leads to destabilisation of the 1 MLCT bands in the visible absorption spectrum, significantly so for the homoleptic complex [Ru(btz) 3 ] 2+ .…”
Section: Introductionmentioning
confidence: 99%
“…These energies can be determined or inferred spectroscopically, electrochemically and computationally and as [Ru(N^N) 3 ] 2+ complexes invariably have a highest occupied molecular orbital of predominantly metallic 4d character, and hence effectively the same ground state, these excited state energies can be readily compared). Work in our laboratory, [26][27][28] and those of others, [29][30][31][32] has shown that complexes containing 1,2,3-triazole rings that lack such steric promotion can also lead to photochemical reactivity, possibly through destabilisation of the 3 MLCT state with respect to the 3 MC state when compared to those states of the archetypal complex [Ru(bpy) 3 ] 2+ . We recently reported the series of complexes [Ru(bpy) 3-n (btz) n ] 2+ (btz = 1,1'-dibenzyl-4,4'-bi-1,2,3-triazolyl, n = 1 to 3) 33 in which an increasing number of btz ligands leads to destabilisation of the 1 MLCT bands in the visible absorption spectrum, significantly so for the homoleptic complex [Ru(btz) 3 ] 2+ .…”
Section: Introductionmentioning
confidence: 99%
“…Due to the magnetically unique nature of each triazole ring environment we propose the identity of this second species to be the solvento complex cis ‐[Os(κ 2 ‐btz) 2 (κ 1 ‐btz)(NCMe)] 2+ ( cis ‐ 3 b ) which is isomeric with trans ‐ 3 b . An intermediate of this type is implicated in the previously reported photolysis of [Ru(bpy) 2 (btz)] 2+ to yield cis ‐[Ru(bpy) 2 (NCCH 3 ) 2 ] 2+ , and many other similar conversions, but where no such species is observed . NMR resonances assigned to a similar intermediate have been observed, albeit at trace levels, during the photolysis of the complex [Ru(bpy) 2 (dmbpy)] 2+ (dmbpy=3,3′‐dimethyl‐2,2′‐bipyridyl) where the photodechelation of the dmbpy ligand is sterically “spring‐loaded” to occur and rechelation is presumably hindered for the same reason.…”
Section: Figurementioning
confidence: 85%
“…In acetonitrile 1 forms both cis ‐ and trans ‐ 2 b whereas in pyridine only trans ‐ 2 a is observed. We would expect the trans isomers to be the more thermodynamically stable based on previous reports . Product formation will depend on the kinetically controlled evolution of the geometry on the excited state potential energy surface but also on the steric demands and therefore accessibility to coordination of the incoming solvent ligand.…”
Section: Figurementioning
confidence: 87%
“…2 It is well known that heterocycles containing nitrogen atoms are effective and stable complexing agents with several metal ions such as copper, cobalt, nickel, manganese and iron. 3 The ability of the nitrogen atom to act as a withdrawing atom decreases the repulsion force between adjacent hetero-rings, allowing construction of supramolecular structures with sophisticated architectures.…”
mentioning
confidence: 99%